CHEST WALL RECONSTRUCTION FOR STERNUM COMPLICATIONS IN CARDIOVASCULAR SURGERY: A SYSTEMATIC REVIEW - Maia Neto, José Dalvo; Jucá, Fabiano; dos Reis, Thomas Dominik de Souza; Martins, Elmiro Heli; Carvalho, Francisco de Assis Montenegro; Machado, João Carlos Fechine; Ricarte, João Pedro Barreto; Lobo Filho, Heraldo Guedis (Seven Editora, 2025)
Introduction: Sternal suture dehiscence represents a serious complication after cardiac surgery, with an incidence ranging from 0.5% to 5% of median sternotomy procedures. This condition is associated with high morbidity and mortality rates, often requiring reconstructive surgical intervention. Muscle flaps, particularly the pectoralis major and rectus abdominis, constitute fundamental therapeutic options for the definitive treatment of this complication. Objective: To conduct a systematic review of the literature on the use of muscle flaps in the reconstruction of mediastinal suture dehiscence after cardiac surgery, with emphasis on pectoralis major and rectus abdominis flaps, analyzing indications, surgical techniques, outcomes, and complications. Methodology: Systematic literature review in PubMed, MEDLINE, Scopus, Web of Science, and LILACS databases, including articles published between 2010 and 2024. Studies addressing sternal dehiscence reconstruction with muscle flaps were selected, focusing on pectoralis major and rectus abdominis. The analysis included data on epidemiology, risk factors, surgical techniques, success rates, and complications. Results: The literature demonstrates that pectoralis major flaps present success rates between 85-95%, being the first choice for anterior and lateral mediastinal defects. The rectus abdominis flap, with success rates of 80-92%, is indicated for extensive defects of the lower third of the sternum. Significant risk factors include diabetes mellitus, obesity, bilateral use of internal mammary artery, COPD, and deep infection. Mortality associated with mediastinitis ranges from 10% to 47% in recent literature. Conclusion: Pectoralis major and rectus abdominis flaps represent effective and safe reconstructive options for treating sternal suture dehiscence. Flap selection should consider the location and extent of the defect, patient clinical conditions, and surgical team experience. Multidisciplinary approach and early treatment are fundamental for reducing morbidity and mortality. A systematized safety algorithm is proposed to optimize the management of this complication. DOI: https://doi.org/10.56238/sevened2025.036-126